2010
DOI: 10.1002/chem.200902527
|View full text |Cite
|
Sign up to set email alerts
|

Dihydronaphthalene‐Fused Boron–Dipyrromethene (BODIPY) Dyes: Insight into the Electronic and Conformational Tuning Modes of BODIPY Fluorophores

Abstract: A new series of boron-dipyrromethene (BDP, BODIPY) dyes with dihydronaphthalene units fused to the beta-pyrrole positions (1a-d, 2) has been synthesised and spectroscopically investigated. All the dyes, except pH-responsive 1d in polar solvents, display intense emission between 550-700 nm. Compounds 1a and 1b with a hydrogen atom and a methyl group in the meso position of the BODIPY core show spectroscopic properties that are similar to those of rhodamine 101, thus rendering them potent alternatives to the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 76 publications
11
72
0
Order By: Relevance
“…We performed assays to examine whether Toxoplasma is able to take up neutral lipids from host LD. In lipid trafficking studies, BODIPY-fatty acids are routinely used and have been shown to incorporate into LD and be readily metabolized by living cells to phospholipids, DAG, TAG and CE [4952]. We incubated infected cells with C4-BODIPY-C9, which has the fluorophore BODIPY 500/510 linked within the fatty acid chain, to track the internalization of this fatty acid analog into the parasite.…”
Section: Resultsmentioning
confidence: 99%
“…We performed assays to examine whether Toxoplasma is able to take up neutral lipids from host LD. In lipid trafficking studies, BODIPY-fatty acids are routinely used and have been shown to incorporate into LD and be readily metabolized by living cells to phospholipids, DAG, TAG and CE [4952]. We incubated infected cells with C4-BODIPY-C9, which has the fluorophore BODIPY 500/510 linked within the fatty acid chain, to track the internalization of this fatty acid analog into the parasite.…”
Section: Resultsmentioning
confidence: 99%
“…In this first report nine different tetraarylazadipyrromethenes were described using these routes. 15 N labelled derivatives of 4a and 6a showed that in the overall conversion of 1a into 3a, two related pathways are ongoing concurrently; the first involves a dimerization of in situ formed 3,5-diphenyl-2H-pyrrol-2-imine 7, and the other reaction of 7 with 2,4-diphenylpyrrole 4a (Scheme 3). condensation between the corresponding aromatic aldehyde and substituted acetophenone.…”
Section: 4mentioning
confidence: 99%
“…Later, a direct modification was made to provide ster ical hindrances for rotation of meso phenyl substitu ents that led to emergence of strong fluorescence of the corresponding dipyrrin complexes containing mesityl groups instead of phenyl rings [20][21][22]. It was shown subsequently in the works [23,24] that, in con trast to meso aryl substitution, the introduction of mobile aromatic groups at the periphery of pyrrole rings of the ligand may result in opposite effect, enhancement of complex fluorescence. Number and positions of aryl substituents in pyrrole rings may play an important role.…”
mentioning
confidence: 99%